Advances in neuropharmacology - Bagetta, Giacinto (International review of neurobiology, 2009)
This volume provides a wide overview of important new advances in the field of Neuropharmacology. In 20 chapters, contributors from all over the world are discussing topics like endocannabinoid function, pain, stress, astrocytes etc, and new possibilities for treatments of neurological diseases with neuropharmacological approaches. - Cutting edge articles in Neuropharmacology - Discusses new possibilities for treatments of neurological disorders - Very international authorship providing a global view of the state of research.